Construction and characterization of a knock-down RNA interference line of OsNRPD1 in rice (Oryza sativa ssp japonica cv Nipponbare). (30th March 2020) - Debladis, Emilie; Lee, Tzuu-Fen; Huang, Yan-Jiun; Lu, Jui-Hsien; Mathioni, Sandra M.; Carpentier, Marie-Christine; Llauro, Christel; Pierron, Davy; Mieulet, Delphine; Guiderdoni, Emmanuel; Chen, Pao-Yang; Meyers, Blake C.; et al.
Abstract : In plants, RNA-directed DNA methylation (RdDM) is a silencing mechanism relying on the production of 24-nt small interfering RNAs (siRNAs) by RNA POLYMERASE IV (Pol IV) to trigger methylation and inactivation of transposable elements (TEs). We present the construction and characterization of osnrpd1, a knock-down RNA interference line of OsNRPD1 gene that encodes the largest subunit of Pol IV in rice ( Oryza sativa ssp japonica cv Nipponbare). We show that osnrpd1 displays a lower accumulation of OsNRPD1 transcripts, associated with an overall reduction of 24-nt siRNAs and DNA methylation level in all three contexts, CG, CHG and CHH. We uncovered new insertions of known active TEs, the LTR retrotransposons Tos17 and Lullaby and the long interspersed nuclear element-type retrotransposon Karma. However, we did not observe any clear developmental phenotype, contrary to what was expected for a mutant severely affected in RdDM. In addition, despite the presence of many putatively functional TEs in the rice genome, we found no evidence of in planta global reactivation of transposition. This knock-down of OsNRPD1 likely led to a weakly affected line, with no effect on development and a limited effect on transposition. We discuss the possibility that a knock-out mutation of OsNRPD1 would cause sterility in rice. This article is part of a discussion meeting issue 'Crossroads between transposons and gene regulation'.